2018
DOI: 10.1186/s40535-018-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of ICT and tourism for improved promotion of tourist attractions in Ethiopia

Abstract: Background Information and communication technology (ICT) is revolutionizing the lives of people and operations of business organizations. Business organizations use ICT to process, store, disseminate, and promote their products and services globally. Beginning from the introduction of the internet, people have been accessing any information at anytime from anywhere. Hence, it is becoming inevitable to live without the aid of ICT. Being the world's largest economic endeavor, tourism is enhancing economies of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…Firstly, the study found out that perceived relative advantage had a significant positive effect on ICT usage (H1a). The finding is consistent with Wagaw and Mulugeta (2018). Based on these findings, it can be extracted that the favorable opinion of users with regard to ICT usage may enhance employee's effectiveness toward achieving higher performance goals.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Firstly, the study found out that perceived relative advantage had a significant positive effect on ICT usage (H1a). The finding is consistent with Wagaw and Mulugeta (2018). Based on these findings, it can be extracted that the favorable opinion of users with regard to ICT usage may enhance employee's effectiveness toward achieving higher performance goals.…”
Section: Discussionsupporting
confidence: 80%
“…TOE theory provides a useful analytical framework in determining factors influencing ICT usage (Oliveira and Martin, 2011). The main assumptions of the theory is that decision to use new ICT system within the organization is determined by three (TOE) factors namely; technological, environmental and organizational factors (Adeola and Evans, 2019;Bahrini and Qaffas, 2018;Kante et al 2017;Kilangi, 2012;Kim and Kim 2018;Lama et al 2018;Wagaw and Mulugeta, 2018). Technological Factors (TF) refers to means of accessing, processing, and distributing volumes of data in the organization, and hence it aids thought process during decision-making (Gastelú et al 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Competitive pressure refers to the extent to which the organisation is being pressured by its competitors in the industry (Oliveira and Martins, 2010). Wagaw and Mulugeta (2018) advocated that users pay more intention to use ICT in tourism when they believe that their competitive advantages will be significantly improved by technology. Hence, the following hypotheses are proposed:…”
Section: Conceptual Developmentmentioning
confidence: 99%
“…Th is advanced technology not only has aff ected signifi cantly how governments and industries operate but also have infl uenced and replaced some traditional means of both human communication/interactions and consumption of products and services (i.e., government services, education, healthcare, entertainment, and leisure) (Hays et al, 2012;OECD, 2019;Ruiz et al, 2018;Sunkel & Trucco, 2011;UNCTAD, 2014). For instance, in the travel and tourism sectors, the ICTs have considerably contributed to improving organizational structures and developing more eff ective marketing strategies to successfully promote tourist attractions and services (Kim-S et al, 2017;Kim-Y et al, 2009;Souto, 2015;Wagaw & Mulugeta, 2018). However, the resulting impacts of ICTs implementation on economic development, innovation, productivity, competitiveness, and market participation is unequal across countries, tourism types (i.e., rural vs. urban destinations), tourism companies (i.e., SEMs), and tourism sectors, especially in accommodation, recreational centers, travel insurance and culinary tourism sectors, where the usage of ICTs showed positive impacts in comparison with other travel sectors (Aramendia-Muneta & Ollo-López, 2013;Jung et al, 2013;Najafi pour et al, 2019;Sedmak et al, 2016).…”
Section: Icts In the Tourism Industrymentioning
confidence: 99%